The Effect of Number of Teeth and Chewing Ability on Cognitive Function of Elderly in UAE: A Pilot Study - Zahra Seraj; Dana Al-Najjar; Mohammed Akl; Noorelrahman Aladle; Yousif Altijani; Ahmed Zaki; Sausan Al Kawas (Hindawi Limited, 2017)
Cognitive decline is one of the major causes of disability among the aging population. The aim of this study was to explore the relationship between oral health parameters (number of teeth, chewing ability, and presence of a denture) and cognitive function in the elderly across the UAE. Fifty persons (age ≥ 60; 71.26 ± 10.23) were enrolled in the study. Cognitive status was assessed using the standardized mini-mental state examination (SMMSE) and accordingly, cognitively normal subjects scoring ≥24 were considered as the control group and cognitively impaired individuals scoring ≤23 were considered as the low scoring group. Chewing ability was examined, number of teeth was noted, and demographical data was collected. The results of this pilot study showed that individuals with low SMMSE scores were significantly less educated (P<0.01) and had fewer number of remaining teeth (P<0.05) and impaired chewing ability (P<0.05). These results demonstrate a significant link between the number of teeth, chewing ability, and cognitive function. However, this pilot study had its limitations and was the first of its kind in the UAE and Gulf region; therefore, future research addressing the limitations is needed to further explore this association.